(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
The article examines the theoretical and methodological foundations of the use of pedagogical technologies in a digital educational environment, their impact on the quality and effectiveness of education and their importance in the modern educational process, the modernization of the education system in the context of digital transformation, the scientific study of the possibilities of using pedagogical technologies in a digital educational environment, the clarification of their theoretical and methodological foundations, the improvement of practical mechanisms and the determination of their impact on educational effectiveness, the importance of scientific and pedagogical importance, the main factors of the development of the education system in the context of digital transformation, the professional competence of the teacher, information culture and innovative activity, the current issues of introducing interactive and innovative pedagogical technologies, the structural components of the digital educational environment, electronic educational resources, distance learning platforms, multimedia tools and adaptive educational technologies.